THE CULTURE AND LOCAL WISDOM OF THE INDIGENOUS PEOPLE KASEPUHAN SINAR RESMI - Pudjiastuti, Sri Rahayu; Hadi, Nestiyanto; Arfani, Hamdan; Akbar, Reza Purwana; Tajudin, Amran Setia (UNIVERSITAS PAKUAN, 2021)
The indigenous people of Kasepuhan Sinar Resmi are one of the indigenous communities that are members of the Banten Kidul traditional unit, which is located in the Sukabumi district, West Java. This study aims to: Identify the living conditions and their philosophies, social and cultural conditions of the people of Kasepuhan Sinar Resmi and Identify the local wisdom of the Kasepuhan Sinar Resmi residents and their implementation in daily life. To study the local wisdom values of the Kasepuhan Sinar Resmi, using a descriptive-qualitative method by conducting analysis and literature review. This study found that local cultural values serve as the basis for the daily life of the Kasepuhan indigenous people. As a farming community, Kasepuhan residents obey the rules of their ancestors by carrying out various traditional rituals related to agricultural activities. The philosophy of life of the Kasepuhan indigenous people, in treating nature, is a form of local wisdom that is maintained by the Kasepuhan indigenous people. The development of technology and information may affect the sustainability of the cultural values of the Kasepuhan indigenous people. The results of this study are expected to provide benefits in the form of: Understanding the philosophy of life as the basis for local wisdom of the community; and As a consideration in determining policies related to indigenous peoples.